2006
DOI: 10.1051/0004-6361:20064894
|View full text |Cite
|
Sign up to set email alerts
|

On the X-ray, optical emission line and black hole mass properties of local Seyfert galaxies

Abstract: We investigate the relation between X-ray nuclear emission, optical emission line luminosities and black hole masses for a sample of 47 Seyfert galaxies. The sample, which has been selected from the Palomar optical spectroscopic survey of nearby galaxies (Ho et al. 1997a, ApJS, 112, 315), covers a wide range of nuclear powers, from L 2−10 keV ∼ 10 43 erg/s down to very low luminosities (L 2−10 keV ∼ 10 38 erg/s). Best available data from Chandra, XMM-Newton and, in a few cases, ASCA observations have been con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

69
469
7
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(558 citation statements)
references
References 109 publications
69
469
7
1
Order By: Relevance
“…In Paper I we report that in our sample of 20 Seyferts, 7/10 type 2 Seyferts are Compton-thick and 13 Seyferts (10 type 1s and 3 type 2s) are Compton-thin. Using the median values of Rx Compton−thin and Rx Compton−thick in this sample, we estimated the absorption correction factor f cor ∼ 70, which is close to the one reported in Panessa et al (2006) by using similar flux diagnostic method but considering the flux ratios of Seyfert type 1s and type 2s rather than that of Compton-thick and Compton-thin sources. We caution that the true value of the correction factor ( f cor ) may be different for different sources depending upon the true value of the absorbing column density.…”
Section: Using X-ray Luminositysupporting
confidence: 58%
“…In Paper I we report that in our sample of 20 Seyferts, 7/10 type 2 Seyferts are Compton-thick and 13 Seyferts (10 type 1s and 3 type 2s) are Compton-thin. Using the median values of Rx Compton−thin and Rx Compton−thick in this sample, we estimated the absorption correction factor f cor ∼ 70, which is close to the one reported in Panessa et al (2006) by using similar flux diagnostic method but considering the flux ratios of Seyfert type 1s and type 2s rather than that of Compton-thick and Compton-thin sources. We caution that the true value of the correction factor ( f cor ) may be different for different sources depending upon the true value of the absorbing column density.…”
Section: Using X-ray Luminositysupporting
confidence: 58%
“…The largest uncertainty in the AGN luminosity function is in the fraction of Compton thick AGN. The fraction of these objects in the local Universe is high: 30-50% of the optically selected Seyfert 2 galaxies can be Compton thick (≈1/4−1/3 of the full AGN population, Risaliti et al (1999), Panessa et al (2006), a result confirmed by hard X-ray selection, see Malizia et al 2009). At higher redshift, the fraction of Compton thick AGN is more uncertain, but it can be as high as one third of the full AGN population (Fiore et al , 2009), or even higher (Daddi et al 2007;Treister et al 2010).…”
Section: Error Budgetsmentioning
confidence: 95%
“…The [O III] line intensity in NGC 4845 is 5.40 × 10 −15 erg s −1 (Ho et al 1997). According to the X-ray -[O III] λ5007 relationship (Panessa et al 2006) the estimated unabsorbed 2-10 keV flux should be 6 × 10 −14 erg s −1 . However, since the X-ray flux observed in January 2011 was almost 1000 times larger (Table 4), the absorption explanation is ruled out.…”
Section: Phenomenologymentioning
confidence: 99%